Agronomic and economic evaluation of permanent raised beds, no tillage and straw mulching for an irrigated maize-wheat system in Northwest India - Ram, Hari; Singh, Yadvinder; Saini, K.S.; Kler, D.S.; Timsina, J.; Humphreys, E.J. (Cambridge University Press, 2012)
No-tillage and raised beds are widely used for different crops in developed countries. A field experiment was conducted on an irrigated maize-wheat system to study the effect of field layout, tillage and straw mulch on crop performance, water use efficiency and economics for five years (2003–2008) in northwest India. Straw mulch reduced the maximum soil temperature at seed depth by about 3 °C compared to the no mulch. During the wheat emergence, raised beds recorded 1.3 °C higher soil temperature compared to the flat treatments. Both maize and wheat yields were similar under different treatments during all the years. Maize and wheat planted on raised beds recorded about 7.8% and 22.7% higher water use efficiency than under flat layout, respectively. Straw mulch showed no effect on water use and water use efficiency in maize. The net returns from the maize-wheat system were more in no tillage and permanent raised beds than with conventional tillage. Bulk density and cumulative infiltration were more in no tillage compared with conventional tillage.